Deficiency of Duffy Antigen Receptor for Chemokines Ameliorated Cochlear Damage From Noise Exposure - Edderkaoui, Bouchra; Sargsyan, Liana; Hetrick, Alisa; Li, Hongzhe (Frontiers in Molecular Neuroscience, 2018)
Cochlear inflammatory response to various environmental insults, including acoustic and ototoxic overexposures, has been increasingly become a topic of interest. As the immune response is associated with both pathology and protection, targeting specific components of the immune response is expected to dissect the relationships between cellular damage and inflammation-associated protection and repair in the cochlea. Duffy antigen receptor for chemokines (DARC) is a member of a group of atypical chemokine receptors, and essential for chemokine-regulated leukocyte/neutrophil trafficking during inflammation. Previous studies have reported that Darc deficiency alters chemokine bioavailability and leukocyte homeostasis, leading to significant anti-inflammatory effects in tissues following injury. In this study, we have used Darc knockout mice to determine the impact of a deficiency in this gene on cochlear development, as well as function in cochlea subjected to various stresses. We observed that DARC is not required for normal development of cochlear function, as evidenced by typical hearing sensitivity in juvenile Darc-KO mice, as compared to wild type C57BL/6 mice. However, Darc-KO mice exhibited improved hearing recovery after intense noise exposure when compared to wild-type. The auditory brainstem response (ABR) threshold shift between KO and wild type mice was most obvious at one-week post-noise exposure. At cochlear locations above frequency range of the energy band of damaging noise, both hair cell survival and ribbon synapse density were improved in Darc deficient animals. In addition, the mRNA levels of some major inflammatory effectors, including Mcp-1 and Gdf15, were altered in Darc-KO mice compared to control mice at one, three and seven days post noise exposure. These data collectively suggest that the normal Darc-dependent inflammatory response slows down the process of hearing recovery, and exacerbates cellular damage in the cochlea after noise exposure.